2021
DOI: 10.1002/sce.21662
|View full text |Cite
|
Sign up to set email alerts
|

Qualitatively different ways of unpacking visual representations when teaching intermolecular forces in upper secondary school

Abstract: Since visual representations play a particularly important role in the teaching and learning of chemistry, the exploration described in this article focuses on them. This is an explorative study of the qualitatively different ways that visual representations can be unpacked by Swedish upper secondary school chemistry teachers dealing with intermolecular forces. Unpacking is characterized as the ways that visual representations get used to open up the possibility of having the critical aspects and features of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…30,31 Investigations in this area also highlight the need for a critical analysis of teacher-centered versus student-centered instructional strategies used to guide students in the unpacking/packing of chemical representations. 28,108 Existing research in chemistry education has shown the positive effects that different types of tasks, such as comparecontrast 109 and drawing activities 13,25 as well as tasks that take advantage of adaptive technologies 110 or embodied cognition 111,112 (e.g., gestures, simulated action), have on different aspects of students' representational competency in chemistry. These investigations, however, typically do not consider how the distinctive characteristics and dimensions of different chemical representations interact with task characteristics to affect student performance.…”
Section: ■ Conclusion and Implicationsmentioning
confidence: 99%
“…30,31 Investigations in this area also highlight the need for a critical analysis of teacher-centered versus student-centered instructional strategies used to guide students in the unpacking/packing of chemical representations. 28,108 Existing research in chemistry education has shown the positive effects that different types of tasks, such as comparecontrast 109 and drawing activities 13,25 as well as tasks that take advantage of adaptive technologies 110 or embodied cognition 111,112 (e.g., gestures, simulated action), have on different aspects of students' representational competency in chemistry. These investigations, however, typically do not consider how the distinctive characteristics and dimensions of different chemical representations interact with task characteristics to affect student performance.…”
Section: ■ Conclusion and Implicationsmentioning
confidence: 99%
“…Phenomenography involves studying other people's experiences (Marton & Booth, 1997), focusing on What is experienced and How it is experienced (Marton & Booth, 1997;Patron et al, 2021;Patron, 2022). Essential in phenomenography is that a person can only experience and act according to how the person experiences the world.…”
Section: Phenomenographymentioning
confidence: 99%
“…Within the framework of phenomenography, learning is about experiencing aspects of the world in particular ways (Marton & Booth, 1997;Lo, 2012;Nilsson & Vikström, 2015;Pang & Marton, 2013;Patron et al, 2021;Patron, 2022). Ways of experiencing things are described as the structure of awareness, which Marton and Booth (1997) equal to structure consciousness.…”
Section: Learning According To Phenomenographymentioning
confidence: 99%
See 2 more Smart Citations